Thermal resistance of interlocking block wall with infill - Muhammad Asyraf , Zulkifli (2015)
In the era of global warming and decreasing resources material today, the awareness of the important of the energy efficient building have increased. A lot of studies about thermal insulation material and thermal conductivity have been carried out to find the solution due to global warming. Interlocking block or Compress Stabilized Earth Block (CSEB) have been widely use today due to its effectiveness especially in reducing the cost and time. Sawdust and polystyrene can act as thermal insulation and hence the usage of sawdust and polystyrene as thermal insulation in building can decrease the waste material from the construction. This study have been carried out to determine the thermal conductivity of interlocking block wall with three different type of infill which are sawdust, polystyrene and polystyrene mix with cement. The thermal resistance test have been conduct based on MS 1532:2002 using guarded hot box method. The higher the R-value or thermal resistance reading means the better the thermal resistance of the material. The result for the sawdust as infill is 1.71 m^2 K/kW, polystyrene infill is 2.12 m^2 K/kW, and polystyrene mix with cement is 1.54 m^2 K/kW. The results show that wall with polystyrene as infill have better thermal insulation than sawdust as infill and polystyrene mix with cement as infill